Industrial packaging performance indicator using a group multicriteria approach: An automaker reverse operations case - Marcelo Miguel da Cruz; Rodrigo Goyannes Gusm\~ao Caiado; Renan Silva Santos (Logistics, 2022)
Background: Due to the growing integration between the various logistics entities and other internal operations, packaging management in the automotive industry is becoming increasingly important from the strategic point of view of the logistics operations of automakers. Performance evaluation of reverse operations is also necessary for managers to know their efficiency, avoid unnecessary resource use and promote circular thinking, enabling more sustainable supply chains. Methods: This research proposes a group decision-making (GDM) approach to evaluate packaging performance in automakers to assist return activities in developing countries. The reverse flow in an automaker was mapped, and by combining literature and empirical views of a packaging engineering team of a Brazilian company, a multicriteria indicator for performance evaluation of packaging was elaborated. It was prioritized through the analytic hierarchy process (AHP)-GDM method, combining judgments to establish a structured technical consensus. Results: It was possible to integrate multiple views of packaging engineering specialists within the same company to know which packaging deserves greater attention from managers when implementing reverse operations from a circular perspective. Conclusions: To demonstrate applicability, this composite indicator also aims to be a quick application approach, considering the restricted time and availability of the specialists in their daily routines.
Keywords: 650; AHP-GDM; automakers; automotive industry; packaging development; reverse logistics